Recursos naturales, diversificación y crecimiento regional en el Perú - Tello, Mario D. (2015)
Based upon the export product space, this paper shows the main features of the export product composition of Peru and its regions. With respect to export baskets, these include: a high con- centration in few commodities; a relatively low degree of similarity between products; relatively high levels of productivity at the international level, and; enormous undiscovered or untapped export potential. In addition, this paper analyzes the hypothesis that the natural resource curse affects regional growth, employment and export diversification. Subject to the limitations of the data and the heterogeneous panel methods employed, estimation results indicate that the share of natural capital out of the total tangible wealth and natural capital per capita seems, on average and in a relatively statistically robust way, to spur growth, primary employment and export concentration in a few products. Consequently, the natural resource curse for the Peruvian regions is not about growth but about low regional development, since such resources do not have a significant impact on secondary and tertiary employment or on export product diversification.